Mesoporous silica nanoparticles enhance seedling growth and photosynthesis in wheat and lupin. (June 2016) - Sun, Dequan; Hussain, Hashmath I.; Yi, Zhifeng; Rookes, James E.; Kong, Lingxue; Cahill, David M.
Abstract: The application of mesoporous silica nanoparticles (MSNs) as a smart delivery system to agricultural crops is gaining attention but the release of nanoparticles into the environment may pose a potential threat to biological systems. We investigated the effects of MSNs on the growth and development of wheat and lupin plants grown under controlled conditions. We report a dramatic increase in the growth of wheat and lupin plants exposed to MSNs. We also found that, in leaves, MSNs localised to chloroplasts and that photosynthetic activity was significantly increased. In addition, absorption and cellular distribution of MSNs by the two plant species following root uptake were observed using scanning electron microscopy equipped with energy dispersive spectroscopy (SEM-EDS). Following uptake of MSNs at 500 and 1000 mg L −1, there was enhancement of seed germination, increased plant biomass, total protein and chlorophyll content. Treatment of both species with MSNs at the highest concentration (2000 mg L −1 ) did not result in oxidative stress or cell membrane damage. These findings show that MSNs can be used as novel delivery systems in plants and that over the range of concentrations tested, MSNs do not have any negative impacts on plant growth or development. Graphical abstract: Highlights: MSNs accumulated in different parts of treated plants following root uptake. The internalization of MSNs with isolated chloroplasts was confirmed. MSNs did not cause oxidative stress or cell membrane damage. MSNs facilitated the photosynthetic activity and growth of the tested plants.